Le sfumature del sottinteso nella narrativa di Carlo Emilio Gadda - Janusz, Joanna (Romanica Silesiana)
Joanna Janusz proves that the unsaid is the means ordering texts by Carlo Emilio Gadda at the intra- extra- and intertextual level. Keywords: Italian novel; oblique statements; narrative levels; intertextuality